Finance-growth-crisis nexus in Asian emerging economies: Evidence from VECM and ARDL assessment - Takashi Fukuda; Jauhari Dahalan (International Journal of Economic Sciences and Applied Research, 2012)
This paper examines the causal relationship between financial development, economic growth and financial crisis in the five Asian emerging economies (India, Indonesia, South Korea, Malaysia and Thailand) during the period 1982 to 2007. All of these countries are known as emerging economies with well known financial crisis episodes (i.e., India's 1991 crisis and the Asian 1997 crisis). The summary indicators of financial development, financial crisis and financial repression are constructed through the principal component approach. The cointegration and Granger causality analysis are conducted by using two techniques of vector error correction model (VECM) and autoregressive distributed lag (ARDL). The main findings are: (1) the direction of the finance-growth nexus is country-specific; (2) deeper financial development can lead to financial crisis; and (3) financial crisis has a negative impact on economic growth (except Korea for the last two). On policy implication, we ascertain that the growth effect of financial deepening should be appraised with the view that financial deepening could gravitate toward financial crisis.
Keywords: E44; O16; O53; 330; finance-growth nexus; financial crisis; Asia; VECM; ARDL; Finanzsektor; Wirtschaftswachstum; Finanzmarktkrise; Schwellenländer; Indien; Indonesien; Südkorea; Malaysia; Thailand